Investigation of Toxoplasma gondii, Neospora caninum and Tritrichomonas foetus in abortions of cattle, sheep and goats in Turkey: Analysis by real-time PCR, conventional PCR and histopathological methods - Irehan, Bunyamin; Sonmez, Ayse; Atalay, Muge Metin; Ekinci, Aysel Itik; Celik, Figen; Durmus, Nalan; Simsek, Sami (Elsevier Sci Ltd, 2022)
The aim of this study was to identify Neosopora caninum, Toxoplasma gondii and Tritricomonas foetus in all cattle aborted fetus samples and N. caninum and T. gondii in sheep and goat aborted fetuses sent to Elazig Veterinary Control Institute during two years. Total genomic DNAs were obtained using a commercial kit. Real-time PCR analysis was performed separately for each agent. Conventional PCR was set up for confirmation of positive samples. Then, fetal brain, heart, lung and liver samples were analysed by hematoxylin-eosin (HE) and Avidin-Biotin Complex (ABC) Immunohistochemistry (IHC) methods. Totally, we tested 55 aborted fetus sam-ples. Of these samples, seven (12.7 %) was belonged to goats, 18 (32.7 %) to sheep and 30 (54.5 %) to cattle. T. gondii was detected in six (10.90 %) samples, and four (7.27 %) of them were positive with Real-time PCR, while only one of these four samples was positive for both classical PCR and IHC. N. caninum was determined by at least one of the three tests in 14 (25.45 %) of the samples studied, while 8 (14.54 %) of the positive samples were detected by Real-time PCR, only two of them were also positive with conventional PCR, eight (14.54 %) samples was determined as positive by IHC. Considering T. foetus in the samples, positivity was determined in two (3.63 %) of 55 aborted fetus (both of which were aborted cattle fetus) by Real-time PCR, while only one of them was positive with conventional PCR, while no positivity was detected with the IHC.
Keywords: Neospora caninum; Toxoplasma gondii; Tritrichomonas foetus; Abortion; Real-time PCR; Immunohistochemistry